2006
DOI: 10.1002/anie.200602143
|View full text |Cite
|
Sign up to set email alerts
|

Taming a Functional Group: Creating Air‐Stable, Chiral Primary Phosphanes

Abstract: No rings of fire! Enantiopure primary phosphanes have been developed which are remarkably stable to air oxidation in both solid and solution states (see example). This new class of stable ligand synthon appears to owe its stability to conjugation in their aryl backbones with the extended π ring system. Even one extra ring is good enough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…The anomalous air-stability of the primary and secondary phosphines 2 and 3 remains unexplained, especially in comparison to tertiary phosphine 4, which is moderately air-sensitive in solution [22]. Although an earlier study reported that 4 did not react with some early transition metal complexes [4d], and octahedral complexes have not yet been obtained, it readily formed square planar Pt(P(CH 2 Fc) 3 ) 2 Cl 2 (14) as a mixture of cis and trans isomers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The anomalous air-stability of the primary and secondary phosphines 2 and 3 remains unexplained, especially in comparison to tertiary phosphine 4, which is moderately air-sensitive in solution [22]. Although an earlier study reported that 4 did not react with some early transition metal complexes [4d], and octahedral complexes have not yet been obtained, it readily formed square planar Pt(P(CH 2 Fc) 3 ) 2 Cl 2 (14) as a mixture of cis and trans isomers.…”
Section: Discussionmentioning
confidence: 95%
“…Calc. for C 22 22.4 (d,J = 30,CH 2 ). IR: 2384IR: (broad), 2355IR: (shoulder), 1122IR: , 1081IR: , 1045IR: , 1020.…”
Section: (Fcch 2 ) 2 Ph(bh 3 ) (7)mentioning
confidence: 98%
“…The palladium-catalyzed cross-coupling of rac-6 with ethyl phenylphosphinate gave a 46 % yield of the monophosphrous compound rac-7 as a mixture of diastereomers (axial chirality and P-centered chirality). [13] l 3 -Phospha[7]helicene rac-9, which has a phosphole moiety, was obtained by the reduction of rac-7 with LiAlH 4 [13c, 14] and a subsequent palladium-catalyzed intramolecular P-arylation. As the phosphorus center of rac-9 is susceptible to oxidation under ambient conditions, rac-9 was directly oxidized without purification to give racemic l 5 -phospha[7]helicene rac-1, which has a phosphole oxide moiety, in a 34 % overall yield from rac-7.…”
mentioning
confidence: 99%
“…It is not clear, using the Barder–Buchwald model12a why oxidation of 2a cannot readily proceed from the axial lone pair on phosphorus in 2a , we note only that both types of ligand consist of a conformationally restricted sterically hindered phosphane. A marked dichotomy in primary phosphane stability was also recently described by Gilheany and co‐workers 12b. A unifying concept that explains the unusual stability of certain phosphanes is elusive although clearly the introduction of one aryl group (contrasting 2b to 2a ) contributes significantly to the stability of ligand 2a .…”
Section: Resultsmentioning
confidence: 70%